The Participation of God and the Torah in Early Kabbalah - Afṭerman, Adam (Religions, 2021)
All Abrahamic religions have developed hypostatic and semi-divine perceptions of scripture. This article presents an integrated picture of a rich tradition developed in early kabbalah (twelfth-thirteenth century) that viewed the Torah as participating and identifying with the Godhead. Such presentation could serve scholars of religion as a valuable tool for future comparisons between the various perceptions of scripture and divine revelation. The participation of God and Torah can be divided into several axes: the identification of Torah with the Sefirot, the divine gradations or emanations according to kabbalah; Torah as the name of God; Torah as the icon and body of God; and the commandments as the substance of the Godhead. The article concludes by examining the mystical implications of this participation, particularly the notion of interpretation as eros in its broad sense, both as the “penetration” of a female Torah and as taking part in the creation of the world and of God, and the notion of unification with Torah and, through it, with the Godhead.